2020
DOI: 10.1007/s00423-020-02040-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 lockdown on a bariatric surgery waiting list cohort and its influence in surgical risk perception

Abstract: Purpose The COVID-19 outbreak has forced a 2-month lockdown (LD) in Spain. We aimed to assess how that had affected our cohort of bariatric patients waiting for surgery. Methods A review of electronic records and a structured phone interview with each patient were conducted. Changes in severity of obesity were analyzed using the Obesity Surgery Score (OSS) and changes in health-related quality of life (HRQoL) using the validated EQ-5D questionnaire. Other miscellaneous questions about behavior modifications an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…The majority of patients have struggled for many years with noninvasive measures like diet, exercise, and pharmacotherapy before surgery. The current COVID-19 pandemic, with its high morbidity and mortality, has led to the cancellation of millions of surgeries, including all bariatric surgery procedures [ 10 , 11 ]. Many centers were afraid to resume activity due to the risk of contamination for patients with morbid obesity or additional deterioration of their pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients have struggled for many years with noninvasive measures like diet, exercise, and pharmacotherapy before surgery. The current COVID-19 pandemic, with its high morbidity and mortality, has led to the cancellation of millions of surgeries, including all bariatric surgery procedures [ 10 , 11 ]. Many centers were afraid to resume activity due to the risk of contamination for patients with morbid obesity or additional deterioration of their pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found a mild increase in patients’ BMI before and after the lockdown period (42.7 vs. 43.2). In our study, there was no statistically significant difference in the mean BMI before and after the period of social isolation (43.2 vs. 43.3) [ 7 ].…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, it was also observed in the study that social distancing resulted in a reduction of fear of confronting and being negatively judged by others [ 6 ]. An effect of a mild increase in BMI (42.7 vs. 43.2) after 2 months of lockdown was observed in a Spanish study including 51 patients from the bariatric surgery waiting list [ 7 ]. Reliable data on the influence of COVID-19 pandemic lockdown on bariatric patients during qualification for surgical treatment in east-central Europe is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these studies revealed that throughout the confinement period, the symptoms of some diseases, such as Alzheimer's [29], diabetes [30] or chronic obstructive pulmonary disease (COPD) [31], were exacerbated. It is well known that health care can be affected during health emergencies and pandemics as a result of resources being diverted towards more urgent areas [32][33][34].…”
Section: Covid-19 Impact On People With Chronic Diseasesmentioning
confidence: 99%